2021
DOI: 10.1007/s41999-021-00523-2
|View full text |Cite
|
Sign up to set email alerts
|

Did the number of older adults with frailty increase during the COVID-19 pandemic? A prospective cohort study in Japan

Abstract: Key summary points Aim This study aimed to clarify the actual frail status over 6 months with the COVID-19 countermeasures based on a prospective cohort study. Findings Pre-frailty and frailty prevalences among Japanese community-dwelling, older adults were 55.0 and 7.9% at the baseline, and 57.3 and 11.8% at the follow-up respectively. Frailty over the 6 months could be predicted by increasing age and multimorbidity during the COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
11
0
3
Order By: Relevance
“…Several lines of evidence now attest that SARS-CoV-2 has a devastating impact on older adults, by increasing several folds their risk of unfavourable outcomes such as the need of hospitalization, respiratory support, intensive care, and ultimately magnifying their risk of death [ 4 ]. Last but not least, increased frailty and loss of function are commonplace in older people after recovering from COVID-19, thus generating dramatic consequences on healthcare, society and economy, since these older patients may need closer follow-up, as well as reinforced functional and psychologic support [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence now attest that SARS-CoV-2 has a devastating impact on older adults, by increasing several folds their risk of unfavourable outcomes such as the need of hospitalization, respiratory support, intensive care, and ultimately magnifying their risk of death [ 4 ]. Last but not least, increased frailty and loss of function are commonplace in older people after recovering from COVID-19, thus generating dramatic consequences on healthcare, society and economy, since these older patients may need closer follow-up, as well as reinforced functional and psychologic support [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that older adults who live alone and are not socially active are more likely to experience incidental frailty/disability due to decreased physical activity during the COVID-19 pandemic. A study, which examined whether the number of older Japanese adults with frailty increased during the COVID-19 pandemic, found that the prevalence of frailty was 7.9% at baseline and 11.8% at follow-up, suggesting an increase in frailty ( Shinohara et al, 2021 ). These previous studies suggest that reduced social interaction because of fewer opportunities to go out due to the spread of COVID-19 may increase the number of older adults with frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Recente estudo demonstrou que a taxa de transição da pré-fragilidade para a fragilidade em 593 idosos residentes no Japão, na pandemia, foi de 9,9% (Shinohara et al, 2021). Para esses autores, o aumento pode ser justificado pelas medidas de prevenção ao coronavírus, além do acréscimo da idade e morbidade durante esse período (Shinohara et al, 2021).…”
Section: íNdice De Fragilidade De Tilburg -Parte B (Ift)unclassified
“…Recente estudo demonstrou que a taxa de transição da pré-fragilidade para a fragilidade em 593 idosos residentes no Japão, na pandemia, foi de 9,9% (Shinohara et al, 2021). Para esses autores, o aumento pode ser justificado pelas medidas de prevenção ao coronavírus, além do acréscimo da idade e morbidade durante esse período (Shinohara et al, 2021). Dessa forma, é possível que medidas de isolamento social restrinjam, ainda mais, a autonomia dos idosos e tenha maior impacto nessa população fragilizada (Xue et al, 2008).…”
Section: íNdice De Fragilidade De Tilburg -Parte B (Ift)unclassified
See 1 more Smart Citation